POSISI DAN PERAN PEREMPUAN BANTEN DALAM PERSPEKTIF GENDER - Devan Rizki Maulana; Ahmad Kholibi; Syarif Hidayatullah; Ahmad Maftuh Sujana (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
In the Banten Province region, which is known for its cultural and social diversity, gender dynamics are very important to understand. Although women in Banten contribute significantly to various aspects of life, such as economic, social, and political, they often face challenges related to patriarchal gender norms. Historically, women in Banten have played an important role in social and economic life. This research method uses a qualitative approach with the aim of deeply understanding the experiences, views, and perceptions of women in Banten regarding their position and role in society. Data collection techniques were carried out through interviews and also using the Focus Group Discussion (FGD) method, which was held with groups of women to discuss issues related to gender, social roles, and the challenges they face. Women in the Banten region contribute significantly to the economic sector, especially in the informal sector. This result can be seen from data from the Banten Central Statistics Agency (BPS) (2021), around 60% of women in Banten work in the informal sector, which often does not provide legal protection and social security. The results of the study show that women's representation in decision-making in Banten is still low. Data from BPS Banten (2021) shows that only around 15% of women hold strategic positions in local government. Barriers faced by women in politics include lack of support from family, gender stereotypes, and lack of access to political education.